The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biomedicines9091241
|View full text |Cite
|
Sign up to set email alerts
|

Cell Properties of Lung Tissue-Resident Macrophages Propagated by Co-Culture with Lung Fibroblastic Cells from C57BL/6 and BALB/c Mice

Abstract: Tissue-resident macrophages (Mø) originating from foetal precursors are maintained by self-renewal under tissue/organ-specific microenvironments (niches). We recently developed a simple propagation method applicable to tissue-resident Mø by co-culturing. Here, we examined the properties of lung tissue-resident Mø propagated by co-culturing with lung interstitial cells. The intracardially and intratracheally perfused lung from BALB/c and C57BL/6 mice could minimise the contamination of alveolar Mø and lung mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous studies have also revealed that (i) testicular interstitial cells and/or tissue-resident Mø produce CSF1, IGF1, and retinoic acid (RA) [ 10 , 12 , 26 ] along with AR and PGR [ 27 , 28 ], which are implicated in spermatogenesis, and (ii) certain tissue-resident Mø express GJA1 [ 29 , 30 ] along with TGFB1 and TGFBR2 [ 21 , 31 ]. Thus, we examined the expression of these molecules and RA synthetic enzymes, i.e., ALDHLA2 and RDH10, in Mø by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also revealed that (i) testicular interstitial cells and/or tissue-resident Mø produce CSF1, IGF1, and retinoic acid (RA) [ 10 , 12 , 26 ] along with AR and PGR [ 27 , 28 ], which are implicated in spermatogenesis, and (ii) certain tissue-resident Mø express GJA1 [ 29 , 30 ] along with TGFB1 and TGFBR2 [ 21 , 31 ]. Thus, we examined the expression of these molecules and RA synthetic enzymes, i.e., ALDHLA2 and RDH10, in Mø by RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed a propagation method for tissue-resident Mø for the liver, lung, spleen, and brain Mø of adult rodents [ 8 , 21 ]. By applying this method with modifications to the adult mouse testis, we successfully propagated testicular tissue-resident Mø by mixed culture with interstitial cells, largely composed of Leydig cells, in standard culture medium containing 10% FBS without additional growth factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we developed a propagation method of tissue-resident Mø by mixed culture with the respective tissue/organ-residing cells that could be applicable for several tissue-resident Mø [ 21 ] and successfully propagated lung interstitial Mø [ 22 ], testicular interstitial Mø [ 23 ], and Kupffer cells [ 24 ], all of which showed identical properties in marker expressions to those in respective ex vivo Mø. In these mixed cultures, tissue-resident Mø could propagate along with the propagation of organ-specific interstitial cells, which behaved as the niche for the respective Mø because these interstitial cells expressed Csf1 , Csf2 , and/or Il34 as growth factors for Mø, as well as marker molecules specific for the respective niche cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mice-originating tissue-resident macrophages specific for lungs were co-incubated with lung interstitial cells in order to study the microenvironment of the expression of specific markers for cell lines studied [ 11 ].…”
mentioning
confidence: 99%